Business Strategy and Performance of SMEs in the Manufacturing Sector - Zakaria Noor Syakirah; Hashim Mohd Khairuddin; Ahmad Sa'ari (2016)
Business strategy is essential to the success of organizations. This implies that in order for organizations such as small and medium-sized enterprises (SMEs) to be successful they need to develop and implement effective business strategy. The review of the strategic management literature however indicates that there is still not much information as well as little research on business strategy in SMEs, particularly in the Malaysian manufacturing sector. This study aims to address this issue by investigating the relationship between business strategy and performance of manufacturing SMEs. The data for the study was collected from 186SMEsin the manufacturing sector by using structured questionnaire. The results of the study show significance relationship between business strategy and performance of the SMEs.